No evidence tube entrapment distresses rodents in typical empathy tests - Dwi Atmoko Agung Nugroho; Sri Kusrohmaniah; Emma Pilz; Clare Krikorian; David Kearns; Burton Slotnick; Maria Gomez; Alan Silberberg (Animal Cognition)
Abstract In the first two experiments an empty tube open at one end was placed in different locations. Male hamsters, tested one at a time, tended to stay close to the tube or in it. During the first minute of the first 4 sessions of Experiment 3, the hamster was unrestrained. If it entered the tube, it was locked within the tube. If it did not enter the tube during the first min, it was placed in it, and the tube was locked. Fifteen min later, the tube was opened, and the hamster was unrestrained for a further 20 min. The tube remained open during Session 5. Hamsters spent more time near the tube than predicted by chance and continued to enter the tube although tube-occupancy duration did not differ from chance levels. In Experiment 4, male rats were tested in two groups: rats in one group had been previously trapped in a tube and rats in the other group allowed to freely explore the test space. For the first two min of each of four 20-min sessions, trapped-group subjects were permitted to move about the chamber unless they entered the tube. In that case, they were locked in for the remainder of the session. If, after two min, they did not enter the tube, they were locked in it for the remaining 18 min. Free rats were unrestricted in all sessions. In Session 5, when both groups were permitted to move freely in the chamber, trapped and free rats spent more time in and near the tube than predicted by chance. These data show tube restraint does not seem to distress either hamsters or rats.